Xenotransplantation. - Soin, B; Vial, C; Friend, P (2000)
BACKGROUND: The success of clinical transplantation has led to a large discrepancy between donor organ availability and demand; considerable pressure exists to develop an alternative source of organs. The use of animal organs for donation is a possible solution that is not yet clinically applicable. METHODS AND RESULTS: A literature review was performed based on a Medline search to find articles on xenotransplantation. Keywords included hyperacute, acute vascular, xenograft rejection combined with concordant and discordant. Additional references cited in these articles from journals not included in Medline were obtained from the British Library. Limited information on unpublished, preliminary work has been included from sources known to the authors, based on their research work in the field. One hundred and forty-six references and four personal communications have been included in this review article. CONCLUSION: A greater understanding of the pathogenesis of xenograft rejection is developing rapidly. Strategies to abrogate hyperacute rejection have proved successful, but control of antibody-driven acute vascular rejection has not yet been achieved. The safety and viability of xenotransplantation as a therapeutic modality are still unproven.